PO12 | Characterisation and real word clinical data of HEM006, a newly formulated intranasal spray desmopressin (DDAVP) to address a global treatment gap (Bleeding, Thrombosis and Vascular Biology, 2025)
Background and Aims: Desmopressin acetate (DDAVP) intranasal spray has been a cornerstone treatment for over three decades in managing bleeding episodes and surgical prophylaxis in patients with von Willebrand disease (VWD) type 1 and non-severe hemophilia A. A recent meta-analysis (>70 studies, 1,770 patients) reported a pooled response rate of 71% (95% CI: 64–78%), with higher efficacy in VWD and some variability across subtypes. Despite its inclusion in the WHO Essential Medicines List for its safety, ease of use, and clinical value, the intranasal formulation (Stimate) was discontinued in 2020, leaving intravenous administration as the only alternative and creating a critical treatment gap. Recent global estimates suggest that over 220,000 bleeding episodes could be prevented annually by DDAVP in type 1 VWD and non-severe hemophilia A patients. New chemical and functional characterization studies, along with real-world clinical data, have been collected to support the development of a newly formulated intranasal DDAVP (HEM006), aimed at addressing the global shortage and restoring access to this essential therapy.